A comparative analysis of the cumulative greenhouse gas emissions and financial viability of residential heating systems located in New York state. (26th October 2022) - Frank, Jenny; Brown, Tristan; Ha, HakSoo; Slade, Dave; Haverly, Martin; Malmsheimer, Robert
Abstract: Achieving the stringent climate goals established by New York State will require significant emissions reductions across the agriculture, commercial and residential, electricity, industry and transportation sectors. This study analyzed the residential heating sector and quantified the environmental and financial impacts of four different residential heating pathways for buildings located in New York State. A conventional ultra‐low sulfur diesel pathway served as the baseline scenario against which three low‐carbon alternative pathways were compared: (1) a 'bioheat' scenario in which biomass‐based diesel is blended with heating oil; (2) a natural gas scenario; and (3) an electric scenario (air‐source heat pump). The low‐carbon alternative heating pathways incorporate the social cost of carbon as an internalized financial benefit from the conventional ultra‐low sulfur diesel baseline scenario. The bioheat pathway yielded the highest net present value (NPV) at $3 684 513 and the electric (air‐source heat pump) pathway had a NPV of $3 618 229. The electric and bioheat scenarios yielded the lowest and second lowest total cumulative emissions at 28545 Mt CO2 e and 51 438 Mt CO2 e, respectively. This study also incorporated a comprehensive sensitivity analysis to depict the impact of: NPV discount rates, fuel costs, carbon intensity values, system installation costs and social cost of carbon values. The study provides policymakers, researchers and other interested stakeholders with a comparison of the environmental and financial impacts of diverse residential heating systems. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.